Recommender system for Real Estate Management - Ginevičius, Tomas; Kaklauskas, Artūras; Kazokaitis, Paulius; Alchimovienė, Jurgita (Business: Theory and Practice, 2011)
The analysis of information, the expert and decision support systems used in real estate management that were developed by researchers from various countries assisted the authors in creating their own Recommender System for Real Estate Management (RSREM). The database of real estate management was developed providing a comprehensive assessment of alternative versions from the economic, technical, technological, infrastructure, qualitative, technological, legislative and other perspectives. Based on the above complex databases, the developed Recommender System for Real Estate Management enables the user to analyse alternatives quantitatively (i.e. a system and subsystems of criteria, units of measure, values and weights) and conceptually (i.e. the text, formula, schemes, graphs, diagrams and videotapes) and provides recommendations.